2016
DOI: 10.17011/ht/urn.201611174654
|View full text |Cite
|
Sign up to set email alerts
|

Detecting fall at home: User-centered design of a pervasive technology

Abstract: Falling is the main cause of domestic accidents and fatal injuries to seniors at home. In this paper, we describe the design process for a new pervasive technology (CIRDO). The aim of this technology is to detect falls (via audio and video sensors) and to alert the elderly's family or caregivers. Two complementary studies were performed. Firstly, the actual risk situations of older adults were analyzed. Secondly, social acceptance was investigated for the different homecare field stakeholders. Our results high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…40 papers mentioned autonomy of the older person with respect to the use of SHHTs. The first sub-theme categorized was in relation to (A) control, which encompassed positive aspects like (possible) empowerment through technology [ 25 , 26 , 73 , 74 ] and negative aspects such as the possibility of technology taking control over the older person, thus increasing dependence [ 55 , 75 ] or decreasing freedom of decision making [ 48 ]. Several studies reported the wishes of older persons to be in control when using the technology (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…40 papers mentioned autonomy of the older person with respect to the use of SHHTs. The first sub-theme categorized was in relation to (A) control, which encompassed positive aspects like (possible) empowerment through technology [ 25 , 26 , 73 , 74 ] and negative aspects such as the possibility of technology taking control over the older person, thus increasing dependence [ 55 , 75 ] or decreasing freedom of decision making [ 48 ]. Several studies reported the wishes of older persons to be in control when using the technology (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, studies reported (B) continuous negotiation between (formal) caregivers’ (professional) responsibilities of care and the opportunities that smart technologies could provide [ 26 , 47 , 55 , 70 , 82 ]. For example, increased need for cooperation between informal and formal caregivers due to technology was foreseen [ 81 ] and fear expressed that over-reliance on female caregivers was exacerbated [ 71 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other social points were related to self-esteem, meaning that older persons needed to reach a certain threshold rst to publicly admit that they need technology (85), or doubts by caregivers if they were able to use the devices (36). This possibly led older persons to prefer unobtrusive technology and those that could not be noticed by visitors (22,55,88).…”
Section: Responsibilitymentioning
confidence: 99%
“…Autonomy 40 papers mentioned autonomy of the older person with respect to the use of SHHTs. The rst sub-theme categorized was in relation to (A) control, which encompassed positive aspects like (possible) empowerment through technology (25,26,73,74) and negative aspects such as the possibility of technology taking control over the older person, thus increasing dependence (55,75) or decreasing freedom of decision making (48). Several studies reported the wishes of older persons to be in control when using the technology (e.g.…”
Section: Privacymentioning
confidence: 99%